2009
DOI: 10.1590/s1516-35982009000600007
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação andrológica por pontos e comportamento sexual em touros da raça Nelore

Abstract: RESUMO -Objetivou-se estudar a relação entre dois métodos de avaliação do potencial reprodutivo -Classificação Andrológica por Pontos (CAP) e comportamento sexual de touros da raça Nelore -e verificar a acurácia desses testes em predizer o potencial reprodutivo dos touros, avaliado pela taxa de gestação ao final da estação de monta, com duração média de 90 dias. Foram utilizados 14 touros, todos classificados como aptos à reprodução, após exame andrológico, CAP e observação do comportamento sexual a campo dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 8 publications
0
5
0
10
Order By: Relevance
“…The average scrotal circumference (38.5±2.4 cm) was considered very good, according to the criteria established by the Brazilian College of Animal Reproduction (1998), similar to those observed by Santos et al (2004) with 37.9 cm in adult Nellore bulls pre-selected for the breeding season and those of Chacón et al (1999) which reported 36.2±4 cm using 598 adult zebu bulls with an average age of 4.2 years. Lopes et al (2009) working with 14 adult Nellore bulls pre-selected for natural mating system with mean age of 50.5±15.7 months, recorded a 37.3±1.5 cm scrotal circumference.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average scrotal circumference (38.5±2.4 cm) was considered very good, according to the criteria established by the Brazilian College of Animal Reproduction (1998), similar to those observed by Santos et al (2004) with 37.9 cm in adult Nellore bulls pre-selected for the breeding season and those of Chacón et al (1999) which reported 36.2±4 cm using 598 adult zebu bulls with an average age of 4.2 years. Lopes et al (2009) working with 14 adult Nellore bulls pre-selected for natural mating system with mean age of 50.5±15.7 months, recorded a 37.3±1.5 cm scrotal circumference.…”
Section: Resultsmentioning
confidence: 99%
“…Chacón et al (1999) observed average below this experiment (61±21%) in adult Nellore bulls. Lopes et al (2009) (CBRA, 1998). Santos et al (2004) and Lopes et al (2009) found 13.8% and 9.5 % of total defects in adult Nelore bulls sound for breeding, respectively, and the means are inferior to this experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, evaluating bulls only as to libido and mounting capacity may lead to inaccurate conclusions, since factors related to the previous experiences of bulls may affect the results of the test (Boyd et al, 1989). Lopes et al (2009) considered that neither the andrological classification in scores nor the sexual behavior assessment were efficient to predict the breeding potential of Nellore bulls in terms of pregnancy rate at the end of the breeding season.…”
Section: Introductionmentioning
confidence: 99%
“…BSE allows the obtaining of information about the potential fertility of bulls, and its importance has been reported by several authors such as Lagerloff (1936), Silva et al (1981), Fonseca et al (1997), Moraes et al (1998), Menegassi et al (2008) and Lopes et al (2009). However, the economic advantages of bull BSE prior to the breeding season still have to be further investigated, because the current studies about bioeconomic impact of technologies are related mainly to beef heifers (Pfeifer et al, 2008) and few of them relate the use of technology with the BSE in bulls.…”
Section: Introductionmentioning
confidence: 94%